A precursor of ternary positive electrode material and preparation method thereof

Through co-precipitation reaction and controlling reaction conditions, a ternary positive electrode material precursor with uniform particle size distribution and high spherical shape is generated, which solves the problems of different sizes and poor stability of the positive electrode material, and improves the circulation performance of lithium-ion batteries.

CN116119737BActive Publication Date: 2025-02-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310105746.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-02-11
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

The particle size distribution of the precursor of the ternary positive electrode material is uneven and the spherical shape is poor, resulting in the problems of different sizes of the positive electrode material after sintering, excessive deliquency and poor stability.

Method used

Crystal nuclei are generated through co-precipitation reaction and continue to grow under different reaction conditions. The particle size distribution and spherical degree of the precursor are controlled to achieve the goal of particle size distribution SPAN of 0.50-0.60 and spherical degree γ of 0.980-0.998.

Benefits of technology

It effectively avoids the poor stability problem caused by the different lithium ion deintercalation depths during the charging-discharge process of the positive electrode material, and improves the overall stability of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116119737B_ABST
    Figure CN116119737B_ABST
Patent Text Reader

Abstract

The present invention provides a precursor of a ternary positive electrode material and a preparation method thereof, which is used to reduce the particle size distribution of the precursor of the ternary positive electrode material and improve the sphericity of the precursor, thereby providing a precursor with uniform size and morphology to improve the stability of the corresponding positive electrode material. The precursor comprises: the molecular formula of the precursor is Ni x Co y Mn z (OH)2; 0.5≤x≤0.95, 0≤y≤0.6, 0≤z≤0.8, x+y+z=1; wherein the particle size distribution SPAN of the precursor is 0.50-0.60, the sphericity γ of the precursor is 0.980-0.998, #imgabs0#γ is the average value of the ratio of the diameter of the maximum cross-section of N precursors to the minimum circumscribed circle diameter of the maximum cross-section, the diameter of the maximum cross-section is the diameter of an equivalent circle having the same circumference as the maximum cross-section, and N≥35.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery positive electrode materials, and in particular to a precursor of a ternary positive electrode material and a preparation method thereof. Background Art

[0002] The cathode materials of lithium-ion batteries mainly include ternary cathode materials such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel cobalt manganese oxide. At present, in terms of improving the performance of lithium-ion batteries by improving the ternary cathode materials, the mainstream is still to optimize the sintering parameters or components of the ternary cathode materials.

[0003] However, the performance of the precursor of the ternary positive electrode material also determines the performance of the ternary positive electrode material to a large extent. For example, when the size of the precursor of the ternary positive electrode material is uneven and the distribution is not concentrated, the problem of excessive sintering of the small-sized precursor is prone to occur in the process of firing the ternary positive electrode material with the precursor; or, even if the preparation of the ternary positive electrode material is successfully completed, the ternary positive electrode material also has the characteristic of non-concentrated size corresponding to the non-concentrated size of the precursor. This leads to the problem of excessive delithiation of the small-sized ternary positive electrode material when the ternary positive electrode material is used in the battery to provide active materials for the battery's charge-discharge, which in turn leads to the problem of poor stability of the ternary positive electrode material. Summary of the invention

[0004] The present invention provides a precursor of a ternary positive electrode material and a preparation method thereof, which are used to reduce the particle size distribution of the precursor of the ternary positive electrode material and improve the sphericity of the precursor, thereby providing a precursor with uniform size and morphology to improve the stability of the corresponding positive electrode material.

[0005] In a first aspect, an embodiment of the present application provides a precursor of a ternary cathode material, comprising:

[0006] The molecular formula of the precursor is Ni x Co y Mn z (OH)2; 0.5≤x≤0.95, 0≤y≤0.6, 0≤z≤0.8, x+y+z=1; where,

[0007] The particle size distribution SPAN of the precursor is 0.50-0.60, and the sphericity γ of the precursor is 0.980-0.998. γ is the average value of the ratios of the diameters of the maximum cross-sections of the N precursors to the diameter of the minimum circumscribed circle of the maximum cross-sections, the diameter of the maximum cross-section being the diameter of an equivalent circle having the same circumference as the maximum cross-section, N≥35.

[0008] The precursor of the ternary positive electrode material has a lower particle size distribution and good sphericity, so it can avoid the problem of different sizes of positive electrode materials fired based on the precursor, and then effectively avoid the problem of poor overall stability of the positive electrode material caused by different depths of lithium ion deintercalation during the discharge-charge process of positive electrode materials of different sizes.

[0009] In a possible implementation manner, the median particle size of the precursor is 10.0-16.0 μm.

[0010] In a possible implementation manner, the ratio between the (001) crystal plane spacing and the (101) crystal plane spacing of the precursor is 1.00-1.10.

[0011] In a possible implementation manner, the cross-sectional porosity of the precursor is 2.50-4.50.

[0012] In a possible implementation manner, the specific surface area of ​​the precursor is 10.0-18.0 m 2 / g.

[0013] In a possible implementation manner, the tap density of the precursor is 1.90-2.05 g / cm 3 .

[0014] In a second aspect, an embodiment of the present application provides a method for preparing a precursor of a ternary positive electrode material, comprising:

[0015] A metal salt solution, a complexing agent solution, and an alkaline solution are subjected to a coprecipitation reaction under a first reaction condition to generate crystal nuclei until a first slurry having a wet solid content of 15-45 g / L is obtained; wherein the solute of the metal salt solution includes a soluble nickel salt, a soluble cobalt salt, and a soluble manganese salt, and the first reaction condition includes a reaction atmosphere in a reaction device; and the reaction atmosphere is nitrogen;

[0016] Allowing the crystal nuclei in the first slurry to continue to grow under the second reaction condition until a second slurry with a wet solid content of 230-270 g / L is obtained; wherein the second reaction condition includes the reaction atmosphere and the second content of the complexing agent; the reaction atmosphere is nitrogen, the second content is greater than the first content, and the first content is the content of the complexing agent in the reaction device under the first reaction condition;

[0017] The crystal nuclei in the second slurry are allowed to continue to grow under the third reaction conditions to obtain a target precursor with a median particle size of 10.0-16.0 μm; wherein the third reaction conditions include a reaction atmosphere, a third pH value, and a third content of the complexing agent; the reaction atmosphere is nitrogen, the third content does not exceed 10 g / L and is not lower than the second content, the difference between the third pH value and the second pH value does not exceed 0.28, and the second pH value is the pH value in the reaction equipment under the second reaction conditions.

[0018] In a possible implementation manner, the median particle size of the crystal nuclei contained in the first slurry is 2.5-3.8 μm; the median particle size of the crystal nuclei contained in the second slurry is 7.5-14.5 μm.

[0019] In a possible implementation manner, the molecular formula of the target precursor is Ni x Co y Mn z (OH)2; 0.5≤x≤0.95, 0≤y≤0.6, 0≤z≤0.8, x+y+z=1; where,

[0020] The particle size distribution SPAN of the precursor is 0.50-0.65, and the sphericity γ of the precursor is 0.980-0.998. γ is the average value of the ratios of the diameters of the maximum cross-sections of the N precursors to the diameter of the minimum circumscribed circle of the maximum cross-sections, the diameter of the maximum cross-section being the diameter of an equivalent circle having the same circumference as the maximum cross-section, N≥35.

[0021] In a possible implementation manner, the complexing agent solution is ammonia water, and the concentration of the ammonia water is 4-6 mol / L; the alkaline solution is sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 5-10 mol / L; the concentration of the metal salt solution is 1.5-2.0 mol / L.

[0022] In a possible implementation manner, the third content of the complexing agent is the same as the second content.

[0023] In a possible implementation manner, the crystal nuclei are allowed to continue to grow under the second reaction conditions until a second slurry having a wet solid content of 230-270 g / L is obtained, comprising:

[0024] Increasing the flow rate of the metal salt solution; wherein the ratio of the increased flow rate of the metal salt solution to the increased flow rate of the metal salt solution is no more than 4;

[0025] Increasing the flow rate of the complexing agent solution and the flow rate of the alkaline solution by the ratio of the increased flow rate of the metal salt solution to the increased flow rate of the metal salt solution, so that the second content of the complexing agent is 5-10 g / L;

[0026] The intermediate pH value in the reaction device is determined, and the intermediate pH value is reduced by 0.3-0.8 for 8-16 hours, so that the crystal nuclei continue to grow under the second reaction conditions to obtain the second slurry.

[0027] In a possible implementation manner, the step of allowing the crystal nuclei in the second slurry to continue to grow under the third reaction conditions to obtain a target precursor having a median particle size of 10.0-16.0 μm comprises:

[0028] The second pH value is lowered to allow the crystal nuclei to grow under the reaction conditions that are reduced by 0.04 every 8 hours on average, to obtain a third slurry including the target precursor; wherein the difference between the third pH value of the third slurry and the second pH value is no more than 0.28. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A low-magnification electron scanning microscope image of the precursor in Example 1 provided in the embodiments of the present application;

[0030] Figure 2 A higher magnification electron scanning microscope image of the precursor in Example 1 provided in the embodiments of the present application;

[0031] Figure 3 A low-magnification electron scanning microscope image of the precursor in Example 2 provided in the embodiments of the present application;

[0032] Figure 4 A higher magnification electron scanning microscope image of the precursor in Example 2 provided in the embodiments of the present application;

[0033] Figure 5 A low-magnification electron scanning microscope image of the precursor in Comparative Example 1 provided in the embodiments of the present application;

[0034] Figure 6 A higher magnification electron scanning microscope image of the precursor in Comparative Example 1 provided in the embodiments of the present application;

[0035] Figure 7 This is a lower magnification electron scanning microscope image of the precursor in Comparative Example 2 provided in the embodiments of the present application. DETAILED DESCRIPTION

[0036] The present invention provides a precursor of a ternary positive electrode material, which is used to provide a precursor with uniform morphology and size, that is, a concentrated particle size distribution and good sphericity, thereby improving the stability of the corresponding ternary positive electrode material. The molecular formula of the precursor is: Ni x Co y Mn z (OH)2; 0.5≤x≤0.95, 0≤y≤0.6, 0≤z≤0.8, x+y+z=1.

[0037] The particle size distribution SPAN of the precursor is 0.50-0.60, and the sphericity γ of the precursor is 0.980-0.998. γ is the average value of the ratios of the diameters of the maximum cross-sections of the N precursors to the diameter of the minimum circumscribed circle of the maximum cross-sections, the diameter of the maximum cross-section being the diameter of an equivalent circle having the same circumference as the maximum cross-section, N≥35.

[0038] It can be seen from the above-mentioned particle size distribution that the ternary positive electrode material provided in the embodiment of the present application has the characteristic of uniform size. At the same time, since the average value γ of the sphericity is close to 1, the morphology of the precursor is uniform, all of which are quasi-spherical, and there is no "bulging" phenomenon on the surface of the precursor, that is, there is no agglomeration. Therefore, the morphology of the ternary positive electrode materials provided in the embodiment of the present application is similar and the size is similar, so it can effectively solve the problem of mismatch between the potential windows of large particles and small particles in the corresponding positive electrode materials, and the inconsistent depth of lithium ion deintercalation. That is, when it is applied to lithium-ion batteries, when a higher potential window is set to adapt to larger particles, the structural damage caused by excessive lithium deintercalation of smaller particles during the charge-discharge process can be avoided, thereby causing the problem of deterioration of the cycle performance of the positive electrode material and lithium-ion battery; at the same time, it can also avoid the problem that when a lower potential window is set to adapt to smaller particles, the lithium ions of larger particles cannot be fully deintercalated, resulting in low capacity.

[0039] For ease of understanding, the following first focuses on D 90 , D 50 , D 10 Provide explanation.

[0040] In D 90 , D 50 , D 10 Both are used to indicate the size of a certain type of particle in a powder material, and D indicates the diameter of the powder particle. Specifically, D 10 Indicates the particle size corresponding to the cumulative particle size fraction of 10% in the material; that is, the particle size is smaller than D 10 The number of particles in the material accounts for 10%. 50 Indicates the particle size corresponding to the cumulative particle size fraction of the material reaching 50%; that is, the particle size is smaller than D 50The number of particles in the material accounts for 50%. 90 Indicates the particle size corresponding to 90% of the cumulative particle size fraction in the material; that is, the particle size is smaller than D 90 The number of particles in the material accounts for 90%.

[0041] Next, taking N=35 as an example, the sampling of the above-mentioned precursor particles is described: First, the above-mentioned precursor particles are sectioned using an argon ion polisher. Then, the sectioned material powder is placed under a scanning electron microscope and observed at a magnification of 1.00K. 35 largest sections are randomly selected for measurement, and the sphericity of each largest section is calculated in turn to obtain the average value.

[0042] Furthermore, the median particle size of the above-mentioned precursor is 10.0-16.0 μm.

[0043] Furthermore, the closer the ratio of the (001) crystal plane spacing to the (101) crystal plane spacing of the precursor is to 1, the higher the degree of crystallization, the more stable the structure of the positive electrode material corresponding to the precursor, and the better the DCR. Therefore, in one embodiment of the present application, the ratio of the (001) crystal plane spacing to the (101) crystal plane spacing of the precursor is 1.00-1.10.

[0044] Furthermore, the cross-sectional porosity of the above precursor is 2.50-4.50. The specific surface area is 10.0-18.0m 2 / g. Tap density is 1.90-2.05g / cm 3 .

[0045] Based on the same inventive concept, the present application embodiment provides a method for preparing a ternary cathode material precursor, which is used to efficiently prepare a precursor with uniform particles. The method includes the following implementation steps:

[0046] Step 101: allowing a metal salt solution, a complexing agent solution, and an alkaline solution to undergo a coprecipitation reaction under a first reaction condition to generate crystal nuclei until a first slurry having a wet material solid content of 15-45 g / L is obtained.

[0047] The first reaction condition includes the reaction atmosphere in the reaction device, the first pH value of the slurry in the reaction device, and the first content of the complexing agent in the reaction device, and the first content is the content of the complexing agent in the (reaction) slurry in the reaction device. The first pH value is 10.80-12.00, and the first content is 2-6 g / L.

[0048] The solute of the metal salt solution includes a soluble nickel salt, a soluble cobalt salt and a soluble manganese salt. The molar concentration of the metal ions in the metal salt solution is 1.5-2.0 mol / L.

[0049] The soluble nickel salt is selected from at least one of nickel sulfate, nickel nitrate, and nickel chloride. The soluble manganese salt is selected from at least one of manganese sulfate, manganese nitrate, and manganese chloride. The cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride.

[0050] The above-mentioned complexing agent solution can be ammonia water or glycine.

[0051] When the complexing agent solution is ammonia water, the concentration of the ammonia water is 4-6 mol / L.

[0052] The alkaline solution may be a sodium hydroxide solution or a potassium hydroxide solution.

[0053] When the alkaline solution is a sodium hydroxide solution, the concentration of the sodium hydroxide solution is 5-10 mol / L.

[0054] Specifically, in step 101, the reaction conditions in the reaction equipment are controlled to be the first reaction conditions, so that the crystal nuclei are generated under the first reaction conditions of high alkalinity (first pH value), non-oxygen (nitrogen), and low complexing agent (first content of complexing agent). This is because when the content of the complexing agent is low, the complexing ability of the metal ions is poor, which leads to a large supersaturation of the slurry in the reaction equipment, and then the crystal nucleus generation rate is significantly higher than the crystal nucleus growth rate; and when the crystal nucleus is in the generation stage, it is at a slower rate to avoid the agglomeration of the crystal nucleus, thereby ensuring that the morphology sphericity of the target precursor finally obtained is good.

[0055] Furthermore, based on the low complexing agent content (ie, the first content), the first pH value is at a strong alkaline level (10.8-12.0), which can increase the rate of crystal nucleation, thereby further increasing the rate of crystal nucleation.

[0056] Therefore, in step 101, on the basis of avoiding the agglomeration of crystal nuclei, the number of crystal nuclei in the reaction device is rapidly increased through the first reaction condition.

[0057] Furthermore, in order to make the crystal nucleus in the aforementioned first reaction condition at the beginning of the coprecipitation reaction, in one embodiment of the present application, before the salt solution and the complexing agent are introduced into the reaction device (e.g., reactor), clean water is first added into the reaction device and the temperature is raised to 50-70°C which is conducive to the coprecipitation reaction. Then, ammonia water and sodium hydroxide solution are introduced so that the content of the complexing agent contained in the reaction system in the reaction device is 2-6 g / L. At the same time, nitrogen is introduced into the reaction device so that the nitrogen content in the reaction device is not less than 99%. The nitrogen flow rate is 2-7m 3 / h. Then, the metal salt solution is introduced into the reaction device, and the alkaline solution and ammonia water are continuously introduced to allow a coprecipitation reaction to occur in the reaction device for 6-12 hours, until the wet solid content of the reaction slurry tested is 15-45g / L, and it is determined that the number of crystal nuclei in the current slurry has reached the target value, and then the first slurry is determined to be obtained.

[0058] The solid content of the wet material is obtained by extracting the reaction slurry from the reaction equipment for testing. The specific testing method is, first, filtering the slurry to obtain the wet material (water-containing solid solution). Then, testing the volume of the water-containing solid solution. Finally, drying the water-containing solid solution in an oven at 100-120°C to obtain a dry material. Testing the mass of the dry material; then the ratio of the mass of the dry material to the volume of the wet material is the solid content of the wet material.

[0059] The median particle size D of the crystal nuclei in the first slurry 50 Therefore, in this step, the reaction node can also be determined by testing the slurry crystal nuclei, that is, when the median particle size of the crystal nuclei in the slurry reaches 2.5-3.8 μm, the slurry is determined to be the first slurry, and there is no need to measure the solid content of the wet material.

[0060] Step 102: allowing the crystal nuclei in the first slurry to continue to grow under the second reaction conditions until a second slurry with a wet material solid content of 230-270 g / L is obtained.

[0061] The second reaction condition includes the reaction atmosphere, the second pH value, and the second content of the complexing agent. The reaction atmosphere remains unchanged and is still nitrogen, and is still at 2-7 m 3 Nitrogen is introduced at a flow rate of / h so that the nitrogen content in the reaction equipment (including the reaction slurry) is not less than 99%.

[0062] In step 102, in order to make the crystal nuclei grow stably and rapidly, the flow rate of the reaction solution (mixed salt solution, alkaline solution, complexing agent solution) can be appropriately increased, and the first pH value can be reduced to the second pH value, so that the crystal nuclei in the reaction slurry enter a stable growth period: the growth rate is much greater than the crystal nucleus generation rate.

[0063] In one embodiment of the present application, the pH in the reaction device (including the reaction slurry) is always controlled by the flow rate of the alkaline solution. The following is a specific description when the alkaline solution is a sodium hydroxide solution and the complexing agent solution is ammonia water:

[0064] First, the flow rate of the metal salt solution is increased, wherein the ratio of the flow rate of the metal salt solution after the increase to the flow rate of the metal salt solution before the increase is no more than 4.

[0065] Then, according to the ratio of the flow rate of the metal salt solution after the increase to the flow rate of the metal salt solution before the increase, the flow rate of the sodium hydroxide solution is increased year by year.

[0066] After increasing the flow rate of the sodium hydroxide solution, the increased flow rate of ammonia added to the reaction device is still determined according to the ratio of the flow rate of the metal salt solution after the increase to the flow rate of the metal salt solution before the increase, and the ammonia content in the reaction device is increased to the increased flow rate of ammonia determined above in 4-8 hours, so that the ammonia content in the reaction device (i.e., the second content of the complexing agent) is 5-10 g / L. That is, according to the ratio of the flow rate of the metal salt solution after the increase to the flow rate of the metal salt before the increase, the flow rate of ammonia is increased so that the second content of the complexing agent in the reaction device after the increase does not exceed 4 compared with the second content before the increase. Next, the pH value in the reaction device is determined, and the pH value is reduced by 0.3-0.8 in 8-16 hours, so that the crystal nucleus can continue to grow in a pH and complexing environment that is easy to grow, until a second slurry with a wet solid content of 230-270 g / L is obtained.

[0067] The time for adjusting the ammonia content and pH in the reaction equipment here is determined according to the target precursor, that is, the size of the crystal nuclei in the second slurry corresponding to the target precursor in step 102. For example, when the median particle size of the crystal nuclei in the second precursor is 12.0 μm, the pH is reduced by 0.3-0.8 within 16 hours, and the ammonia content is controlled to rise to 5-10 g / L within 4 hours.

[0068] The median particle size of the crystal nuclei in the second slurry is 7.5-14.5 μm.

[0069] Step 103: allowing the crystal nuclei in the second reaction slurry to continue to grow under the third reaction condition to obtain a target precursor with a median particle size of 10.8-18.0.

[0070] The third reaction condition includes a reaction atmosphere, a third pH value, and a third content of the complexing agent.

[0071] The reaction atmosphere remains unchanged, nitrogen, and is still at 2-7m 3 Nitrogen is introduced at a flow rate of / h so that the nitrogen content in the reaction equipment (including the reaction slurry) is not less than 99%.

[0072] After step 101, the number of crystal nuclei in the reaction slurry increases, and the size of the crystal nuclei in the reaction slurry increases in step 102. When entering step 103, the solid content in the slurry in the reaction equipment is already at a high level, and the metal salt solution is metal ions (e.g., Ni + ,Co 2+ , Mn 2+) concentration is also at a high level, which leads to an increase in the nucleation driving force in the slurry. In this case, although the nucleation of crystals still requires a high pH environment, the pH required for nucleation of crystals is reduced compared to normal conditions (for example, when the solid content is low in the initial stage of the reaction). Therefore, in order to avoid the situation in which the nucleation of crystals in step 103 affects the uniformity of the target product, the second pH value of the second reaction condition must be continuously and stably reduced until the target precursor is obtained, and the reduction rate is 0.02-0.06 per unit time, and the unit time is not less than 8 hours; for example, 16 hours. That is, in one embodiment of the present application, the crystal nucleus is grown under the reaction condition that the second pH value is reduced by 0.04 every 8 hours on average, and a third slurry including the target precursor is obtained; wherein the difference between the third pH value of the third slurry and the second pH does not exceed 0.28. At the same time, since the lower the content of the complexing agent, the higher the supersaturation in the slurry, the third content of the complexing agent is not lower than the second content, and does not exceed 10g / L. Preferably, the third content of the complexing agent is the same as the second content to avoid uncontrollable influence of supersaturation in the slurry on nucleation. The crystal nuclei continue to grow under the third reaction condition until a target precursor with a median particle size of 10.0-16.0 is obtained.

[0073] The molecular formula of the target precursor is Ni x Co y Mn z (OH)2; 0.5≤x≤0.95, 0≤y≤0.6, 0≤z≤0.8, x+y+z=1; where,

[0074] The particle size distribution SPAN of the precursor is 0.50-0.65, and the sphericity γ of the precursor is 0.980-0.998. γ is the average value of the ratios of the diameters of the maximum cross-sections of the N precursors to the diameter of the minimum circumscribed circle of the maximum cross-sections, the diameter of the maximum cross-section being the diameter of an equivalent circle having the same circumference as the maximum cross-section, N≥35.

[0075] Furthermore, the ratio between the (001) crystal plane spacing and the (101) crystal plane spacing of the above target precursor is 1.00-1.10.

[0076] Furthermore, the cross-sectional porosity of the target precursor is 2.50-4.50; the specific surface area is 10.0-18.0m 2 / g; tap density is 1.90-2.05g / cm 3 .

[0077] The following is a detailed description of Examples 1-4 and Comparative Examples 1-4.

[0078] Example 1

[0079] S1. According to Ni 0.90 Co 0.05 Mn 0.05 (OH)2 stoichiometric ratio, soluble nickel sulfate, cobalt sulfate, and manganese sulfate are prepared into a metal salt solution with a total metal ion molar concentration of 1.5 mol / L. Sodium hydroxide solution is mixed with deionized water in a certain stoichiometric ratio to prepare a precipitant solution with a concentration of 7 mol / L; an ammonia solution with a concentration of 5 mol / L is prepared as a complexing agent solution.

[0080] S2. Add deionized water to the reactor, set the stirring rate to 300r / min, the temperature to 65°C, add ammonia water, adjust the ammonia content in the reactor to 2.0-2.5g / L, add sodium hydroxide solution to adjust the pH value to 10.95, and continuously introduce nitrogen as protective gas into the reactor at a nitrogen flow rate of 5m 3 / h.

[0081] S3, nucleation stage: add metal salt solution, sodium hydroxide solution and complexing agent solution into the reactor, maintain the temperature in the reactor at 65°C, pH at 10.95, the ammonia content in the reactor at 2.0-2.5 g / L, and carry out coprecipitation reaction for 6 hours to obtain the first slurry with a median particle size of 2.6 μm and a wet solid content of 28 g / L.

[0082] S4, stable growth period: the ammonia content in the reactor was increased to 5.0g / L within 8 hours, and the pH value was steadily reduced from 10.95 to 10.55 within 16 hours, and the pH value was controlled to decrease by 0.10 every 4 hours. After that, the reaction conditions were kept stable until the second slurry with a median particle size of 8.0μm and a wet solid content of 245g / L was obtained.

[0083] S5, nuclear sensitive period: maintain the ammonia content in the slurry in the reaction equipment at 5g / L, and gradually reduce the pH within 10 hours, a total reduction of 0.04. Then maintain the ammonia content and pH in the reaction equipment unchanged until the target precursor with a median particle size of 10.20μm is obtained, and stop the feeding reaction.

[0084] S6. After the target precursor is aged in the reactor for 2 hours, it is pumped into a centrifuge, washed by centrifugation at 65°C with 1.5 mol / L sodium hydroxide solution, and dried at 80°C to obtain a dry target precursor. The electron microscope image of the target precursor is shown in Figure 1-Figure 2 .

[0085] The particle size, tap density and sphericity of the target precursor were tested. See Table 1 for the test data.

[0086] S7, weigh 5kg of target precursor and 2.2kg of single crystal lithium hydroxide, put them into a high-speed mixer for mixing, and then put them into a box-type resistance furnace for the following sintering steps. In the resistance furnace, first preheat at 380℃ for 3.5h, then anneal at 580℃ for 5.5h, and finally sinter at 780℃ for 10h, and keep the oxygen atmosphere throughout the process. The obtained product is dissociated and screened to finally obtain the positive electrode material.

[0087] Lithium-ion batteries were prepared using the positive electrode materials and cycle performance tests were performed. The test data is shown in Table 2.

[0088] Example 2

[0089] S1. According to Ni 0.90 Co 0.05 Mn 0.05 (OH)2 stoichiometric ratio, soluble nickel sulfate, cobalt sulfate, and manganese sulfate are prepared into a metal salt solution with a total metal ion molar concentration of 1.5 mol / L. Sodium hydroxide solution is mixed with deionized water in a certain stoichiometric ratio to prepare a precipitant solution with a concentration of 7 mol / L; an ammonia solution with a concentration of 5 mol / L is prepared as a complexing agent solution.

[0090] S2. Add deionized water to the reactor, set the stirring rate to 300r / min, the temperature to 65°C, add ammonia water to make the ammonia content in the reactor 3.0-3.5g / L, add sodium hydroxide solution to adjust the pH value to 10.90, and continuously introduce nitrogen as protective gas into the reactor at a nitrogen flow rate of 5m 3 / h.

[0091] S3, nucleation stage: add metal salt solution, sodium hydroxide solution and ammonia water into the reactor, keep the temperature in the reactor at 65°C, the pH at 10.90, the ammonia content in the reactor at 3.0-3.5 gg / L, carry out coprecipitation reaction for 6 hours, and obtain the first slurry with a median particle size of 3.0 μm and a wet solid content of 28 g / L.

[0092] S4, stable growth period: the ammonia content in the reactor (in the slurry) was increased to 6.0 g / L within 8 hours, and the pH dropped from 10.90 to 10.45 at a relatively stable rate within 16 hours. After that, the reaction conditions were kept stable until the second slurry with a median particle size of 10.0 μm and a wet solid content of 245 g / L was obtained.

[0093] S5, nuclear sensitive period: maintain the ammonia content in the reactor (in the slurry) at 6.0 g / L, and gradually reduce the pH within 8 hours, a total reduction of 0.04. Then maintain the ammonia content and pH in the reaction equipment unchanged until the target precursor with a median particle size of 13.50 μm is obtained, and stop the feeding reaction.

[0094] S6. After the target precursor is aged in the reactor for 2 hours, it is pumped into a centrifuge, washed by centrifugation at 65°C with 1.5 mol / L sodium hydroxide solution, and dried at 80°C to obtain a dry target precursor. The electron microscope image of the target precursor is shown in Figure 3 , Figure 4 .

[0095] The particle size, tap density and sphericity of the target precursor were tested. See Table 1 for the test data.

[0096] S7. Weigh 5 kg of the prepared precursor material and 2.2 kg of single crystal lithium hydroxide and put them into a high-speed mixer for mixing, and then put them into a box-type resistance furnace for the following sintering steps. In the resistance furnace, first preheat at 390°C for 3.5 hours, then anneal at 590°C for 5.5 hours, and finally sinter at 800°C for 10 hours, and keep the oxygen atmosphere throughout the process. The obtained product is dissociated and screened to finally obtain the positive electrode material.

[0097] The above positive electrode materials were used to prepare lithium-ion batteries, and the cycle performance was tested. The test data is shown in Table 2.

[0098] Example 3

[0099] S1. According to Ni 0.90 Co 0.05 Mn 0.05 (OH)2 stoichiometric ratio, soluble nickel sulfate, cobalt sulfate, and manganese sulfate are prepared into a metal salt solution with a total metal ion molar concentration of 1.5 mol / L. Sodium hydroxide solution is mixed with deionized water in a certain stoichiometric ratio to prepare a precipitant solution with a concentration of 7 mol / L; an ammonia solution with a concentration of 5 mol / L is prepared as a complexing agent solution.

[0100] S2. Add deionized water to the reactor, set the stirring rate to 300r / min, the temperature to 65°C, add ammonia water, adjust the ammonia content in the reactor to 4.0-4.5g / L, add sodium hydroxide solution to adjust the pH value to 10.85, and continuously introduce nitrogen as protective gas into the reactor at a nitrogen flow rate of 5m 3 / h.

[0101] S3, nucleation stage: add metal salt solution, sodium hydroxide solution and complexing agent solution into the reactor, maintain the temperature in the reactor at 65°C, pH at 10.85, the ammonia content in the reactor at 4.0-4.5 g / L, and carry out coprecipitation reaction for 6 hours to obtain the first slurry with a median particle size of 3.2 μm and a wet solid content of 28 g / L.

[0102] S4, stable growth period: the ammonia content in the reactor (in the slurry) was increased to 7.0 g / L within 8 hours, and the pH value was reduced from 10.85 to 10.40 at a relatively stable rate within 16 hours. After that, the reaction conditions were kept stable until a second slurry with a median particle size of 12.0 μm and a wet solid content of 245 g / L was obtained.

[0103] S5, nuclear sensitive period: maintain the ammonia value in the reactor (in the slurry) at 7.0 g / L, and gradually reduce the pH within 6 hours, a total reduction of 0.04. Then maintain the ammonia content and pH in the reaction equipment unchanged until the target precursor with a median particle size of 15.00 μm is obtained, and stop the feeding reaction.

[0104] S6. The target precursor is allowed to stand in the reactor for 2 hours, and then pumped into a centrifuge, and washed by centrifugation at 65° C. with a 1.5 mol / L sodium hydroxide solution, and dried at 80° C. to obtain a dry target precursor.

[0105] The particle size, tap density and sphericity of the target precursor were tested. See Table 1 for the test data.

[0106] S7. Weigh 5 kg of the prepared precursor material and 2.2 kg of single crystal lithium hydroxide and put them into a high-speed mixer for mixing, and then put them into a box-type resistance furnace for the following sintering steps. In the resistance furnace, first preheat at 400°C for 3.5 hours, then anneal at 600°C for 5.5 hours, and finally sinter at 810°C for 10 hours. The oxygen atmosphere is maintained throughout the process. The obtained product is dissociated and sieved to finally obtain the positive electrode material.

[0107] The above positive electrode materials were used to prepare lithium-ion batteries, and the cycle performance was tested. The test data is shown in Table 2.

[0108] Example 4

[0109] S1. According to Ni 0.90 Co 0.05 Mn 0.05 (OH)2 stoichiometric ratio, soluble nickel sulfate, cobalt sulfate, and manganese sulfate are prepared into a metal salt solution with a total metal ion molar concentration of 1.5 mol / L. Sodium hydroxide solution is mixed with deionized water in a certain stoichiometric ratio to prepare a precipitant solution with a concentration of 7 mol / L; an ammonia solution with a concentration of 5 mol / L is prepared as a complexing agent solution.

[0110] S2. Add deionized water to the reactor, set the stirring rate to 300r / min, the temperature to 65°C, add ammonia water, adjust the ammonia content in the reactor to 5.0-5.5g / L, add sodium hydroxide solution to adjust the pH value to 10.80, and continuously introduce nitrogen as protective gas into the reactor at a nitrogen flow rate of 5m 3 / h.

[0111] S3, nucleation stage: add metal salt solution, sodium hydroxide solution and complexing agent solution into the reactor, maintain the temperature in the reactor at 65°C, pH at 10.80, the ammonia content in the reactor at 5.0-5.5 g / L, and carry out coprecipitation reaction for 6 hours to obtain the first slurry with a median particle size of 3.6 μm and a wet material solid content of 28 g / L.

[0112] S4, stable growth period: the ammonia content in the reactor (in the slurry) was increased to 8.0 g / L within 8 hours, and the pH value was reduced from 10.75 to 10.30 at a relatively stable rate within 16 hours. After that, the reaction conditions were kept stable until a second slurry with a median particle size of 14.0 μm and a wet solid content of 245 g / L was obtained.

[0113] S5, nuclear removal sensitive period: maintain the ammonia value in the reactor (in the slurry) at 8.0 g / L, and reduce the pH by 0.04 in 4 hours. Then maintain the ammonia content and pH in the reaction equipment unchanged until the median particle size is 18.00 μm, and stop the feeding reaction.

[0114] S6. After the target precursor is allowed to stand in the reactor for 2 hours, it is pumped into a centrifuge, centrifuged and washed with 1.5 mol / L sodium hydroxide solution at 65° C., and dried at 80° C. to obtain a dry target precursor.

[0115] The particle size, tap density and sphericity of the target precursor were tested. See Table 1 for the test data.

[0116] S7. Weigh 5 kg of the prepared precursor material and 2.2 kg of single crystal lithium hydroxide and put them into a high-speed mixer for mixing, and then put them into a box-type resistance furnace for the following sintering steps. In the resistance furnace, first preheat at 410°C for 3.5 hours, then anneal at 620°C for 5.5 hours, and finally sinter at 830°C for 10 hours. The oxygen atmosphere is maintained throughout the process. The obtained product is dissociated and sieved to finally obtain the positive electrode material.

[0117] Lithium-ion batteries were prepared using the positive electrode materials and cycle performance tests were performed. The test data is shown in Table 2.

[0118] Comparative Examples 1-4

[0119] Comparative Examples 1-4 correspond to Examples 1-4 respectively, except that the ammonia value in step S4 remains unchanged, the pH value in step S5 remains unchanged, and the other implementation steps are the same as Examples 1-4.

[0120] Figure 5 , Figure 6 They are respectively SEM images of the target precursor in Comparative Example 1. Figure 7This is the SEM image of the target precursor in Comparative Example 2.

[0121] Table 1

[0122]

[0123] The preparation of lithium ion batteries in the above-mentioned Examples 1-4 and Comparative Examples 1-4 and the cycle performance test conditions are the same. The cycle performance test is specifically described below:

[0124] First, the corresponding positive electrode material, conductive acetylene black, KS-6, and PVDF were mixed in a mass ratio of 94.5%:2%:1%:2.5% to prepare slurry.

[0125] Then, the slurry was applied to the side of the positive electrode sheet (copper foil) opposite to the positive electrode sheet, with a surface density of 15 mg / cm 2 The negative electrode uses artificial graphite, which is homogenized according to the mass ratio of graphite: SP: CMC: SBR = 95.5%: 1%: 1.5%: 2%, and the coating surface density is controlled at 10mg / cm 2 A 20 μm dry PP / PE / PP separator was used as the separator, and a carbonate solution of LiPF6 with a concentration of 1 mol / L was used as the electrolyte to assemble a lithium-ion battery.

[0126] The capacity retention rate of the lithium-ion battery was tested under the conditions of 3.0-4.20 V, 1 C, and 45° C. for 300 charge-discharge cycles. The test data is shown in Table 2.

[0127] Table 2

[0128]

[0129] It can be seen that the first cycle capacity and cycle performance of Examples 1-4 are better than those of Comparative Examples 1-4.

[0130] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

Claims

1. A precursor of a ternary cathode material, characterized in that: include: The molecular formula of the precursor is Ni x Co y Mn z (OH)2; 0.5≤x≤0.95, 0<y≤0.6, 0<z≤0.8, x+y+z=1; where, The particle size distribution SPAN of the precursor is 0.50-0.60, and the sphericity γ of the precursor is 0.980-0.

998. γ is the average value of the ratios of the diameters of the largest cross-sections of the N precursors to the diameter of the smallest circumscribed circle of the largest cross-sections, the diameter of the largest cross-section being the diameter of an equivalent circle having the same circumference as the largest cross-section, N ≥ 35; The ratio between the (001) interplanar spacing and the (101) interplanar spacing of the precursor is 1.00-1.10; The median particle size of the precursor is 10.0-16.0 μm; The cross-sectional porosity of the precursor is 2.50-4.50; The specific surface area of ​​the precursor is 10.0-18.0 m 2 / g; the tap density of the precursor is 1.90-2.05g / cm 3 .

2. A method for preparing a precursor of a ternary cathode material as claimed in claim 1, characterized in that: include: A metal salt solution, a complexing agent solution, and an alkaline solution are subjected to a coprecipitation reaction under a first reaction condition to generate crystal nuclei until a first slurry having a wet solid content of 15-45 g / L is obtained; wherein the solute of the metal salt solution includes a soluble nickel salt, a soluble cobalt salt, and a soluble manganese salt, and the first reaction condition includes a reaction atmosphere in a reaction device; and the reaction atmosphere is nitrogen; Allowing the crystal nuclei in the first slurry to continue to grow under the second reaction condition until a second slurry with a wet solid content of 230-270 g / L is obtained; wherein the second reaction condition includes the reaction atmosphere and the second content of the complexing agent; the reaction atmosphere is nitrogen, the second content is greater than the first content, and the first content is the content of the complexing agent in the reaction device under the first reaction condition; The crystal nuclei in the second slurry continue to grow under the third reaction condition to obtain a target precursor with a median particle size of 10.0-16.0 μm; wherein the third reaction condition includes a reaction atmosphere, a third pH value, and a third content of the complexing agent; the reaction atmosphere is nitrogen, the third content is not more than 10 g / L and is not less than the second content, the difference between the third pH value and the second pH value is not more than 0.28, and the second pH value is the pH value in the reaction device under the second reaction condition; The median particle size of the crystal nuclei contained in the first slurry is 2.5-3.8 μm; the median particle size of the crystal nuclei contained in the second slurry is 7.5-14.5 μm; The crystal nuclei in the first slurry are allowed to continue to grow under the second reaction conditions until a second slurry having a wet solid content of 230-270 g / L is obtained, comprising: Increasing the flow rate of the metal salt solution; wherein the ratio of the increased flow rate of the metal salt solution to the increased flow rate of the metal salt solution is no more than 4; Increasing the flow rate of the complexing agent solution and the flow rate of the alkaline solution by the ratio of the increased flow rate of the metal salt solution to the increased flow rate of the metal salt solution, so that the second content is 5-10 g / L; The pH value in the reaction device is determined, and the pH value is reduced by 0.3-0.8 for 8-16 hours, so that the crystal nuclei continue to grow under the second reaction conditions to obtain the second slurry.

3. The method according to claim 2, characterized in that The complexing agent solution is ammonia water, and the concentration of the ammonia water is 4-6 mol / L; the alkaline solution is sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 5-10 mol / L; the concentration of the metal salt solution is 1.5-2.0 mol / L.

4. The method according to claim 2 or 3, characterized in that The third content of the complexing agent is the same as the second content.

Citation Information

Patent Citations

  • Wet synthesis method of NCMA high-nickel quaternary precursor

    CN111874958A

  • Ternary precursor material and preparation method thereof

    CN115286050A